Eclampsia - Pinargote Chica, Jahaira Estefania (2018)
This clinical case aims to show how through the use of nursing practices it was possible to recover the health of a patient diagnosed with eclampsia, this process involves permanent care and continuous observation of the pregnant woman. Eclampsia is a pathology of the pregnant woman, previously known as uremia, has symptoms such as hypertension, severe headache, agitation among others, the sum of all these problems can lead to clonic seizures that could lead to a Deep coma or to be worse to the loss of the life of the mother and even of her and the being that is in her womb. The objective of the present case study is to apply the nursing process in primigrave of 35 weeks of gestation with diagnosis of eclampsia using interventions according to the taxonomy NANDA, NIC and NOC in the hospital "MATILDE HIDALGO DE PROCEL". And finally, in a certain way, promote the self-care of women in pregnancy, since through it seeks to expose the consequences of this pathology that is potentially harmful, one of the most dangerous causes is not attending the responsible prenatal care which are of great importance during the pregnancy process.